ZAKRES SWOBODY INTERCYZY W ZNOWELIZOWANYCH PRZEPISACH KODEKSU RODZINNEGO I OPIEKUŃCZEGO - Sokołowski, Tomasz (Wydział Prawa i Administracji UAM, 2008)
The most recent amendments to most of the provisions of the Polish matrimonial property law (2005) and the new contents of article 47 § 1 of Polish family and guardianship code support the claim that there is a need for a new construction of this legislation. The new interpretation of the amended provisions presented in this paper has considerably enlarged the scope of freedom of the matrimonial agreement, which corresponds with the new social and economic situation in Poland. The author postulates, firstly, to take into consideration the admissibility of a conditional matrimonial agreement, the matrimonial agreement for a specific period of time and the mixed matrimonial agreement that combines the enlargement of common property with the limitation of its scope, but only in relation to different periods of time. Secondly, there are also a number of important legal and social factors that support the claim for consideration of the admissibility of a combined matrimonial agreement which relates directly to one legal relation. This theory is supported in particular by recent amendments to the legislation of our neighbours: Russia and the Czech Republic.
THE SCOPE OF FREEDOM OF A MATRIMONIAL AGREEMENT IN THE AMENDED PROVISIONS OF THE POLISH FAMILY AND GUARDIANSHIP CODE